The importance of Organizational Commitment to Knowledge Management - Rocha,Felipe de Sequeira (2008)
In recent years, Knowledge Management (KM) has assumed great importance in the literature on business and management. However, we still have so little understanding of the human issues in KM processes. Thus, this research aims to contribute to analysing the importance of Organizational Commitment (OC) to KM. First, we used the Cardoso (2003) Knowledge Management Questionnaire (QGC) that embraces all organizational activities around knowledge processes and distinguishes four dimensions of KM. Secondly we applied the Quijano, Masip, Navarro and Aubert (1997) questionnaire (ASH-ICI) that distinguishes two types of commitment (personal and instrumental) into four dimensions. These two questionnaires were applied with 300 employees in the Portuguese industrial ceramics sector. Through multiple regression analysis we found that levels of organizational commitment are statistically important to KM dimensions. Furthermore, our analysis indicates that personal commitment is more important than need commitment. These results are discussed and Organizational Behaviour specialists and Work and Organizational psychologists are challenged to assume more responsibility and an active role in KM studies and practices and to explore human issues in this field.